The figure of Hermilio Valdizán Medrano inside Peruvian medicine - Huarcaya-Victoria, Jeff (2018)
On January 1918, hundred years ago, two events of great importance for Peruvian medicine took place: the emergence of the first issue of the “Anales de la Facultad de Medicina”, and the inauguration of the Asilo Colonia de la Magdalena, currently known as “Víctor Larco Herrera” Hospital. Among the notable doctors who participated in both events, the figure of Hermilio Valdizán Medrano, father of Peruvian psychiatry, stands out. Graduated from the Faculty of Medicine of the Universidad Nacional Mayor de San Marcos (UNMSM), Valdizán actively participated in the academic world of the early twentieth century, promoting major pedagogical reforms, in addition to his work as a publicist and historian. He also stood out in the psychiatric clinic, introducing the teaching and structured evaluation of mental medicine, based on the Peruvian man. Today, we can appreciate the scope of his great vision, as an advanced for his time, because he rescued people with mental disorders and regained the wisdom of our past before contempt. In this article we present, briefly, the life and academic work of Valdizán, in order to strengthen the identity of Peruvian medicine and Psychiatry.